Cast high-toughness Al-Si alloy capable of remarkably accelerating alloy age hardening response and preparation method of cast high-toughness Al-Si alloy

By adding Zn elements to Al-Si-Mg-Cu alloys and optimizing the heat treatment process, the problems of low efficiency, high cost and high carbon emissions in the existing technology are solved, and the mechanical properties and ageing of alloys are improved in the alloys are achieved. The hardening response accelerates, improving production efficiency and reducing carbon emissions.

CN119464860APending Publication Date: 2025-02-18JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411652945.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing Al-Si-Mg-Cu alloy has low production efficiency, high cost and high carbon emissions, making it difficult to effectively improve the mechanical properties of the alloy and shorten the aging hardening response time.

Method used

By adding Zn elements to the Al-Si-Mg-Cu alloy, the chemical composition and heat treatment process of the alloy are optimized, including solution treatment and aging treatment, significantly accelerating the aging hardening response of the alloy.

Benefits of technology

The improvement of the mechanical properties of the alloy is achieved, shortening the time required to reach peak hardness, improving the production efficiency of castings, and reducing energy consumption and carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464860A_ABST
    Figure CN119464860A_ABST
Patent Text Reader

Abstract

The invention relates to a cast high-toughness Al-Si alloy capable of remarkably accelerating alloy age hardening response and a preparation method of the cast high-toughness Al-Si alloy, and belongs to the technical field of aluminum alloys. The technical problems that in the prior art, an Al-Si-Mg-Cu alloy mechanical property strengthening method is low in production efficiency, high in cost and high in carbon emission are solved. The Al-Si alloy disclosed by the invention is prepared from the following components in percentage by mass: 7.8 percent to 8.0 percent of Si, 0.5 percent to 0.7 percent of Mg, 0.05 percent to 0.2 percent of Cu, 1.8 percent to 3.8 percent of Zn, 0.05 percent to 0.12 percent of Sr, 0.005 percent to 0.03 percent of B and the balance of Al and inevitable impurity elements. Through optimal design of alloy components, it is guaranteed that the alloy has high strength and plasticity, the aging treatment time of the alloy can be remarkably shortened, and the aging treatment efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloys, and in particular relates to a cast high-strength and toughness Al-Si alloy capable of significantly accelerating the aging hardening response of the alloy and a preparation method thereof. Background Art

[0002] With the implementation of the national "dual carbon" strategy, the concepts of energy conservation, emission reduction and green environmental protection have gradually become popular. As an important way to achieve this goal, automobile lightweighting has received widespread attention and attention. Al-Si-Mg-Cu alloys have become one of the key materials for automobile lightweighting due to their low density, good corrosion resistance and excellent casting performance.

[0003] Al-Si-Mg-Cu alloys are heat-treatable alloys, and aging hardening is their most important strengthening mechanism. Through the T6 heat treatment process, when the Al-Si-Mg-Cu alloy is in the peak aging state, high-density, finely dispersed metastable phases such as β” and Q' are precipitated in the matrix. At this time, the alloy will obtain the maximum strength and hardness. Commercial A356 and A319 alloys are improved in their mechanical properties through appropriate heat treatment processes. However, while obtaining the best mechanical properties of the alloy, it usually means a longer heat treatment cycle. Excessive heat treatment time not only greatly affects production efficiency, but also increases production costs. In addition, the large energy consumption during the heat treatment process is usually accompanied by high carbon emissions. This is an issue that cannot be ignored for modern industries that pursue green manufacturing and sustainable development. Therefore, optimizing the heat treatment process, shortening the heat treatment time, and improving the performance of the alloy are important research directions in the production of Al-Si-Mg-Cu alloys. Summary of the invention

[0004] In view of this, the purpose of the present invention is to solve the technical problems of low production efficiency, high cost and high carbon emissions in the mechanical property strengthening method of Al-Si-Mg-Cu alloy in the prior art, and to provide a cast high-strength and toughness Al-Si alloy and a preparation method thereof that can significantly accelerate the aging hardening response of the alloy, which not only effectively improves the mechanical properties of the alloy after heat treatment, but also significantly accelerates the aging hardening response of the alloy, greatly improving the production efficiency of castings.

[0005] The technical solutions adopted by the present invention to achieve the above-mentioned purpose are as follows.

[0006] In the first aspect, the present invention provides a cast high-strength and toughness Al-Si alloy that can significantly accelerate the aging hardening response of the alloy, comprising, by mass percentage: Si: 7.8% to 8.0%, Mg: 0.5% to 0.7%, Cu: 0.05% to 0.2%, Zn: 1.8% to 3.8%, Sr: 0.05% to 0.12%, B: 0.005% to 0.03%, and the remainder is Al and unavoidable impurity elements.

[0007] Preferably, the mass percentage of the unavoidable impurity elements is ≤0.2%.

[0008] In a second aspect, the present invention further provides a method for preparing the above-mentioned cast high-strength and toughness Al-Si alloy that can significantly accelerate the aging hardening response of the alloy, comprising the following steps:

[0009] Step 1: weigh pure Al, pure Mg, pure Zn, Al-Si master alloy, Al-Cu master alloy, Al-Sr master alloy and Al-B master alloy according to proportion;

[0010] Step 2: heat pure Al, Al-Si master alloy and Al-Cu master alloy to 800±2.5°C, and after they are completely melted, cool them to 750±2.5°C and keep them warm to obtain alloy liquid;

[0011] Step 3: Add preheated pure Mg and pure Zn to the alloy liquid, stir evenly and keep warm after they are completely melted;

[0012] Step 4: adding the preheated Al-Sr master alloy and Al-B master alloy to the alloy liquid, stirring evenly and keeping warm after they are completely melted, to obtain a modified alloy liquid;

[0013] Step 5: Add a slag remover to the deteriorated alloy liquid, stir evenly, skim off impurities, pass argon gas for refining, and skim off impurities again;

[0014] Step 6: When the alloy liquid to be modified is cooled to 700±2.5°C, it is poured into a steel mold preheated to 100±2.5°C to obtain a cast alloy;

[0015] Step 7: The cast alloy is solution treated at 535±1°C for 4 hours, quenched to room temperature, and then aged at 180±1°C for 2.5 to 4.5 hours to obtain a cast high-strength and tough Al-Si alloy that can significantly accelerate the alloy aging hardening response.

[0016] Preferably, in step 1, the purity of pure Al is ≥99.9%, the purity of pure Mg is ≥99.9%, and the purity of pure Zn is ≥99.9%.

[0017] Preferably, in step 1, the Al-Si master alloy is Al-20.8wt%Si, the Al-Cu master alloy is Al-50wt%Cu, the Al-Sr master alloy is Al-10wt%Sr, and the Al-B master alloy is Al-3wt%B.

[0018] Preferably, in step 2, the insulation time is 30 minutes.

[0019] Preferably, in step 2, the pure Al, Al-Si master alloy and Al-Cu master alloy are preheated to 200°C±2.5°C.

[0020] Preferably, in step 3, the stirring time is 2 minutes and the insulation time is 5 minutes.

[0021] Preferably, in step 3, the pure Mg and pure Zn are preheated to 200°C±2.5°C.

[0022] Preferably, in step 4, the stirring time is 3 minutes and the insulation time is 15 minutes.

[0023] Preferably, in step 4, the Al-Sr master alloy and the Al-B master alloy are preheated to 200°C±2.5°C.

[0024] Preferably, in step 5, the stirring time is 2 min.

[0025] Preferably, in step 5, the amount of the slag remover is 1wt% of the mass of the modified alloy liquid.

[0026] Preferably, in step 5, the purity of the nitrogen is 99.99%, and the ventilation time of the nitrogen is 2 minutes.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The principle of the present invention is as follows: for Al-Si-Mg-Cu alloys, the improvement of the strength of the alloy under peak aging is mainly attributed to the precipitation strengthening effect. The addition of Zn in the present invention reduces the reaction activation energy of the "β" phase (Mg-Zn clusters can serve as nucleation sites for Mg-Si precipitates, resulting in the formation of high-density Mg-Si precipitates), which promotes the formation of uniformly distributed fine and dispersed β" phases, thereby achieving an enhancement of the alloy aging hardening response.

[0029] Compared with the prior art, the advantages of the present invention are:

[0030] The present invention also proposes the above-mentioned cast high-strength and toughness Al-Si alloy that can significantly accelerate the alloy's aging hardening response. By adding the Zn element, the strength and elongation of the Al-Si-Mg-Cu alloy are effectively improved, and its aging hardening response is accelerated, thereby reducing the effective time required for the alloy to reach peak hardness.

[0031] The present invention also proposes a method for preparing the above-mentioned cast high-strength and toughness Al-Si alloy that can significantly accelerate the alloy aging hardening response, which not only greatly improves the production efficiency of castings, but also reduces energy consumption, and contributes to the realization of green manufacturing and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the embodiments and comparative examples of the present invention, the drawings required for use in the embodiments and comparative examples will be briefly introduced below. Obviously, the drawings described below are only some embodiments and comparative examples of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 The hardness variation curve of the cast alloy prepared in Example 1, Example 2 and Comparative Example 1 of the present invention under the conditions of 535±1℃ / 4h solution treatment + 180±1℃ / 3h aging treatment. DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below in conjunction with embodiments and comparative examples.

[0035] Example 1

[0036] The cast high-strength and toughness Al-Si alloy prepared in this embodiment has the following chemical compositions, by mass percentage: Si: 8%, Mg: 0.6%, Cu: 0.1%, Zn: 1.8%, Sr: 0.08%, B: 0.01%, and the remainder is Al and unavoidable impurities, and the total mass percentage of the impurity elements does not exceed 0.2%.

[0037] The method for preparing the above-mentioned cast high-strength and toughness Al-Si alloy comprises the following steps:

[0038] Step 1: according to the chemical composition of the cast high-strength and toughness Al-Si alloy, pure Al, pure Mg, pure Zn, Al-20.8wt%Si master alloy, Al-50wt%Cu master alloy, Al-10wt%Sr master alloy and Al-3wt%B master alloy were weighed;

[0039] Step 2: pure Al, Al-20wt% Si and Al-50wt% Cu preheated to 200±2.5°C are placed in a crucible, heated to 800±2.5°C in a resistance furnace, and after being completely melted, the temperature of the resistance furnace is lowered to 750±2.5°C and kept warm for 30 minutes to obtain alloy liquid;

[0040] Step 3: Add pure Mg and pure Zn preheated to 200±2.5℃ to the alloy liquid, stir for 2min after it is completely melted, and keep warm for 5min;

[0041] Step 4: Add Al-10wt% Sr and Al-3wt% B preheated to 200±2.5°C to the alloy liquid for modification. After it is completely melted, stir for 3 minutes and keep warm for 15 minutes to obtain a modified alloy liquid.

[0042] Step 5: Add 1wt% of slag remover to the modified alloy liquid, stir for 2 minutes, and then pass high-purity (99.99%) argon gas for 2 minutes to remove the slag on the surface of the modified alloy liquid;

[0043] Step 6: When the temperature of the modified molten metal drops to 720±2.5°C, pour it into a steel mold preheated to 100±2.5°C, and air-cool it to room temperature to obtain a cast alloy;

[0044] Step 7: The cast alloy is placed in a heat treatment furnace, solution treated at 535±1℃ for 4h, then quenched (water quenched) to room temperature, and immediately aged at 180±1℃ to obtain a cast high-strength and tough Al-Si alloy. During the process, the hardness change curve of the cast alloy is as follows: Figure 1 As shown by Figure 1 It can be seen that its aging peak hardness is about 4h, and the mechanical properties under the aging peak state are shown in Table 1.

[0045] The chemical composition of the cast high-strength and toughness Al-Si alloy prepared in Example 1 was tested, and the test results were: Si: 7.83%, Mg: 0.57%, Cu: 0.1%, Zn: 1.87%, Sr: 0.05%, B: 0.01%, Fe: 0.14%; the detection method was GB / T 7999 "Photoelectric Direct Reading Emission Spectroscopy Analysis Method for Aluminum and Aluminum Alloys".

[0046] Example 2

[0047] The cast high-strength and toughness Al-Si alloy prepared in this embodiment has the following chemical compositions, by mass percentage: Si: 8%, Mg: 0.6%, Cu: 0.1%, Zn: 3.6%, Sr: 0.08%, B: 0.01%, and the remainder is Al and unavoidable impurities, and the total mass percentage of the impurity elements does not exceed 0.2%.

[0048] The method for preparing the above-mentioned cast high-strength and toughness Al-Si alloy comprises the following steps:

[0049] Step 1: weigh pure Al, pure Mg, pure Zn, Al-20.8wt% Si, Al-50wt% Cu, Al-10wt% Sr and Al-3wt% B according to the chemical composition of the cast high-strength and toughness Al-Si alloy;

[0050] Step 2: pure Al, Al-20wt% Si and Al-50wt% Cu preheated to 200±2.5°C are placed in a crucible, heated to 800±2.5°C in a resistance furnace, and after being completely melted, the temperature of the resistance furnace is lowered to 750±2.5°C and kept warm for 30 minutes to obtain alloy liquid;

[0051] Step 3: Add pure Mg and pure Zn preheated to 200±2.5℃ to the alloy liquid, stir for 2min after it is completely melted, and keep warm for 5min;

[0052] Step 4: Add Al-10wt% Sr and Al-3wt% B preheated to 200±2.5°C to the alloy liquid for modification. After it is completely melted, stir for 3 minutes and keep warm for 15 minutes to obtain a modified alloy liquid.

[0053] Step 5: Add 1wt% of slag remover to the modified alloy liquid, stir for 2 minutes, and then pass high-purity (99.99%) argon gas for 2 minutes to remove the slag on the surface of the modified alloy liquid;

[0054] Step 6: When the temperature of the modified molten metal drops to 720±2.5°C, pour it into a steel mold preheated to 100±2.5°C, and air-cool it to room temperature to obtain a cast alloy;

[0055] Step 7: The cast alloy is placed in a heat treatment furnace, solution treated at 535±1℃ for 4h, then quenched (water quenched) to room temperature, and immediately aged at 180±1℃ to obtain a cast high-strength and tough Al-Si alloy. During the process, the hardness change curve of the cast alloy is as follows: Figure 1 As shown by Figure 1 It can be seen that its aging peak hardness is about 3h, and the mechanical properties under the aging peak state are shown in Table 1.

[0056] The chemical composition of the cast high-strength and toughness Al-Si alloy prepared in Example 2 was tested, and the test results were: Si: 7.9%, Mg: 0.59%, Cu: 0.11%, Zn: 3.72%, Sr: 0.06%, B: 0.011%, Fe: 0.14%; the detection method was GB / T 7999 "Photoelectric Direct Reading Emission Spectroscopy Analysis Method for Aluminum and Aluminum Alloys".

[0057] Comparative Example 1

[0058] The Al-Si-Mg-Cu alloy prepared in this comparative example has the following chemical compositions, by mass percentage: Si: 8%, Mg: 0.6%, Cu: 0.1%, Sr: 0.08%, B: 0.01%, and the remainder is Al and unavoidable impurities, and the total mass percentage of the impurity elements does not exceed 0.2%.

[0059] The preparation method of the Al-Si-Mg-Cu alloy comprises the following steps:

[0060] Step 1: According to the chemical composition of Al-Si-Mg-Cu-Zn alloy, pure Al, pure Mg, Al-20.8wt%Si, Al-50wt%Cu, Al-10wt%Sr and Al-3wt%B were weighed;

[0061] Step 2: pure Al, Al-20wt% Si and Al-50wt% Cu preheated to 200±2.5°C are placed in a crucible, heated to 800±2.5°C in a resistance furnace, and after being completely melted, the temperature of the resistance furnace is lowered to 750±2.5°C and kept warm for 30 minutes to obtain alloy liquid;

[0062] Step 3: Add pure Mg preheated to 200±2.5℃ to the alloy liquid, stir for 2min after it is completely melted, and keep warm for 5min;

[0063] Step 4: Add Al-10wt% Sr and Al-3wt% B preheated to 200±2.5°C to the alloy liquid for modification. After it is completely melted, stir for 3 minutes and keep warm for 15 minutes.

[0064] Step 5: Add 1wt% of slag remover to the modified alloy liquid, stir for 2 minutes, and then pass high-purity (99.99%) argon gas for 2 minutes to remove the slag on the surface of the modified alloy liquid;

[0065] Step 6: When the temperature of the modified molten metal drops to 720±2.5°C, pour it into a steel mold preheated to 100±2.5°C, and air-cool it to room temperature to obtain a cast alloy;

[0066] Step 7: The cast alloy is placed in a heat treatment furnace, solution treated at 535±1℃ for 4h, then quenched (water quenched) to room temperature, and then immediately aged at 180±1℃ to obtain Al-Si-Mg-Cu alloy. During the process, the hardness change curve of the cast alloy is as follows: Figure 1 As shown by Figure 1 It can be seen that its aging peak hardness is about 6h, and the mechanical properties under the aging peak state are shown in Table 1.

[0067] The chemical composition of the Al-Si-Mg-Cu alloy prepared in Comparative Example 1 was detected, and the test results were: Si: 7.88%, Mg: 0.59%, Cu: 0.11%, Sr: 0.06%, B: 0.011%, Fe: 0.15%; the detection method was GB / T 7999 "Photoelectric Direct Reading Emission Spectroscopy Analysis Method for Aluminum and Aluminum Alloys".

[0068] Depend on Figure 1 It can be seen that the addition of Zn can significantly shorten the time for the alloy to reach the peak hardness of aging while ensuring that the alloy has a high hardness (the time for Comparative Example 1, Example 1, and Example 2 to reach the peak hardness of the alloy is about 6h, 4h, and 3h, respectively), which effectively improves the efficiency of the alloy aging heat treatment.

[0069] Table 1 shows the mechanical properties and aging heat treatment cycles of Examples 1, 2 and Comparative Example 1 under their respective peak aging conditions.

[0070]

[0071] It can be seen from Table 1 that the tensile strength, yield strength and elongation of the alloy with 1.8wt% Zn added (Example 1) are increased by 8.9%, 5.9% and 51.6% respectively compared with the alloy without Zn added (Comparative Example 1). The tensile strength, yield strength and elongation of the alloy with 3.6% Zn added (Example 2) are increased by 11.4%, 7.1% and 56.5% respectively compared with the alloy without Zn added (Comparative Example 1).

[0072] The above results indicate that the present invention, through the optimized design of alloy composition, not only ensures that the alloy has high strength and plasticity, but also can significantly shorten the aging treatment time of the alloy and improve the aging treatment efficiency.

[0073] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the embodiments. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. The obvious changes or modifications derived from them are still within the protection scope of the invention.

Claims

1. Al-Si alloy, characterized in that In terms of mass percentage, Comprising: Si: 7.8% to 8.0%, Mg: 0.5% to 0.7%, Cu: 0.05% to 0.2%, Zn: 1.8% to 3.8%, Sr: 0.05% to 0.12%, B: 0.005% to 0.03%, and the remainder is Al and unavoidable impurity elements.

2. The Al-Si alloy according to claim 1, characterized in that The mass percentage of the unavoidable impurity elements is ≤0.2%.

3. The method for preparing an Al-Si alloy according to any one of claims 1 to 2, characterized in that: The following steps are involved: Step 1: weigh pure Al, pure Mg, pure Zn, Al-Si master alloy, Al-Cu master alloy, Al-Sr master alloy and Al-B master alloy according to proportion; Step 2: heat pure Al, Al-Si master alloy and Al-Cu master alloy to 800±2.5°C, and after they are completely melted, cool them to 750±2.5°C and keep them warm to obtain alloy liquid; Step 3: Add preheated pure Mg and pure Zn to the alloy liquid, stir evenly and keep warm after they are completely melted; Step 4: adding the preheated Al-Sr master alloy and Al-B master alloy to the alloy liquid, stirring evenly and keeping warm after they are completely melted, to obtain a modified alloy liquid; Step 5: Add a slag remover to the deteriorated alloy liquid, stir evenly, skim off impurities, pass argon gas for refining, and skim off impurities again; Step 6: When the alloy liquid to be modified is cooled to 700±2.5°C, it is poured into a steel mold preheated to 100±2.5°C to obtain a cast alloy; Step 7: The cast alloy is solution treated at 535±1°C for 4 hours, quenched to room temperature, and then aged at 180±1°C for 2.5 to 4.5 hours to obtain an Al-Si alloy.

4. The method for preparing an Al-Si alloy according to claim 3, characterized in that: In step 1, the purity of pure Al is ≥99.9%, the purity of pure Mg is ≥99.9%, and the purity of pure Zn is ≥99.9%; In step 1, the Al-Si master alloy is Al-20.8wt%Si, the Al-Cu master alloy is Al-50wt%Cu, the Al-Sr master alloy is Al-10wt%Sr, and the Al-B master alloy is Al-3wt%B.

5. The method for preparing the Al-Si alloy according to claim 3, characterized in that: In step 2, The pure Al, Al-Si master alloy and Al-Cu master alloy are preheated to 200°C±2.5°C; The insulation time is 30 minutes.

6. The method for preparing an Al-Si alloy according to claim 3, characterized in that: In step 3, the pure Mg and pure Zn are preheated to 200°C±2.5°C; The stirring time is 2 min, and the heat preservation time is 5 min.

7. The method for preparing an Al-Si alloy according to claim 3, characterized in that: In step 4, the Al-Sr master alloy and the Al-B master alloy are preheated to 200° C.±2.5° C.; The stirring time is 3 minutes, and the heat preservation time is 15 minutes.

8. The method for preparing an Al-Si alloy according to claim 3, characterized in that: In step 5, the stirring time is 2 min; The amount of the slag remover is 1wt% of the mass of the modified alloy liquid; The purity of the nitrogen is 99.99%, and the ventilation time of the nitrogen is 2 minutes.